Optimizing porous silicon and NGO-based anodes: a pathway to high-capacity and long-cycle lithium-ion batteries - Kalkan, Elanur; Yagci, Ozlem; Eksik, Osman; Yuksel, Sureyya Aydin; Arvas, Melih Besir (ELSEVIER, 2025)
This study investigates the synthesis and electrochemical performance of nitrogen-doped graphene oxide (NGO) and porous silicon (Si) composites as advanced anode materials for lithium-ion batteries (LIBs). Porous silicon was synthesized using n-type crystalline silicon through an anodization method in ethanol, methanol, and propanol-based electrolytes, while NGO was prepared via a one-step chronoamperometry process. Comprehensive characterizations, including FT-IR, XRD, Raman spectroscopy, SEM, BET, and EIS, were conducted to evaluate the structural, morphological, and electrochemical properties of the composite materials. Among the tested systems, the ethanol-based electrolyte showed the most promising results, producing porous silicon with the highest surface area (705.82 m2/g) and optimal pore structure. Electrochemical tests revealed that a 30 % porous silicon addition to NGO achieved the best cycling stability and specific capacity, with an initial discharge capacity of 841 mAh/g at 0.5 A/g, retaining 128 mAh/g after 100 cycles. Pre-lithiation treatment further enhanced cycling stability by mitigating capacity loss associated with solid electrolyte interphase (SEI) formation. These findings underscore the potential of NGO and porous silicon composites synthesized in ethanol-based systems as cost-effective and high-performance anode materials for next-generation LIBs.
Keywords: Nitrogen-doped graphene oxide; Porous silicon; Lithium-ion batteries; Anode materials; Energy storage; Electrochemical performance; Pre-lithiation treatment; LAYER; COMPOSITE; PROGRESS; Energy & Fuels